Fashion’s Final Frontier" : The Correlation of Gender Roles and Fashion in Star Trek - Andres, Katharina (My University, 2013)
Since its creation in 1966, Star Trek has been a dominant part of popular culture and as thus served as the source for many cultural references. Star Trek’s creator Gene Roddenberry wanted to realize his vision of a utopia but at the same time, he used the futuristic setting of the show to comment on the present time, on ac-tual social and political circumstances. This means that each series can be regarded as a mirror image of the time in which it was created. The clothing of the characters in the different series is one part of that image. The uniforms of The Original Series show influences of the 1960s pop art movement as well as the mini-skirt trend that experienced its peak in that decade. In the course of almost 40 years, however, many things changed. In the 1990s, in Deep Space Nine and Voyager, a unisex uniform replaced the mini-dresses, with few exceptions; the colorful shirts gave way to ones that were mostly black. This trend continues into the new century. This essay interprets the evolution of the female officers’ uniforms from femi-nized dresses to androgynous clothing over the development of the series as a reflection of the change of gender roles in contemporary American society. The general functions of the female characters’ uniforms are the central object of its analysis while the few, but noteworthy exceptions to this pattern are given specific attention. Finally, one of the most intriguing lines of enquiry is, how the prequel series Enterprise, supposed to be set before The Original Series, but produced and aired from 2001 to 2005, fits in the picture.
Keywords: 306 Kultur und Institutionen; Star Trek; women; fashion; science fiction; 1960s; backlash